Judicial Considerations in Rendering a Verdict Against a Police Officer in a Premeditated Murder (Case Study of Decision Number 1031/Pid.B/2022/PN.Mks) - Aisyah Bela Islami; Fauziah E. Pometia Rumalutur; Muhammad Gamal T. Laure (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
This study aims to analyze the judicial considerations in imposing criminal sanctions against police officers involved in premeditated murder based on Decision Number 1031/Pid.B/2022/PN.Mks. This research uses a normative-empirical legal research method with statutory and case approaches. Data were collected through literature studies and document analysis, particularly court decisions and relevant legal materials, which were then analyzed qualitatively. The results show that the criminal sanctions imposed on the defendant were based on Article 340 of the Indonesian Criminal Code without any special treatment despite the defendant’s status as a police officer. The judge considered the defendant’s position as a law enforcement officer as an aggravating factor because law enforcement officers are expected to uphold the law and maintain public trust. The decision reflects the principles of justice, legal certainty, and legal utility, as well as the principle of equality before the law.